Keberkesanan Penggunaan Sistem Kawalan Destinasi Lif di dalam Bangunan Komersial - Rosli, Afika; Omar, Roshartini; Sarpin, Norliana; Shafii, Haryati (Research in Management of Technology and Business, 2021)
Elevators in a building are one of the most important means of transportation in a tall building. Differences in elevator systems such as traditional elevator systems and destination control systems affect the effectiveness of users in the building. With this destination control system, it is considered the best compared to traditional but there are shortcomings that affect the efficiency of an elevator journey such as making it difficult to move from one level to another. Therefore, this study aims to examine the effectiveness of the use of destination control systems in commercial buildings, study the problems faced by users in using destination control systems and identify measures to improve the effectiveness of the use of elevator destination control systems in commercial buildings. The method of this study uses the Google Form questionnaire method. Respondents involved were 50 employees and users of the building and analyzed by descriptive statistics through Microsoft Excel 2013. For the level of effectiveness of the use of elevator destination control system data show it can be concluded that the level of effectiveness of the use of elevator destination control systems in commercial buildings is which is encouraging in the use of elevator destination control systems. This study hopes to provide an advantage to users and parties involved to choose a better system.